Cost-Consequence Analysis of Advanced Imaging in Acute Ischemic Stroke Care - Boltyenkov, Artem T.; Martinez, Gabriela; Pandya, Ankur; Katz, Jeffrey M.; Wang, Jason J.; Naidich, Jason J.; Rula, Elizabeth; Sanelli, Pina C. (Frontiers in Neurology, 2021)
Introduction: The purpose of this study was to illustrate the potential costs and health consequences of implementing advanced CT angiography and perfusion (CTAP) as the initial imaging in patients presenting with acute ischemic stroke (AIS) symptoms at a comprehensive stroke center (CSC). Methods: A decision-simulation model based on the American Heart Association's recommendations for AIS care pathways was developed to assess imaging strategies for a 5-year period from the institutional perspective. The following strategies were compared: (1) advanced CTAP imaging: NCCT + CTA + CT perfusion at the time of presentation; (2) standard-of-care: non-contrast CT (NCCT) at the time of presentation, with CT angiography (CTA) ± CT perfusion only in select patients (initial imaging to exclude hemorrhage and extensive ischemia) for mechanical thrombectomy (MT) evaluation. Model parameters were defined with evidence-based data. Cost-consequence and sensitivity analyses were performed. The modified Rankin Scale (mRS) at 90 days was used as the outcome measure. Results: The decision-simulation modeling revealed that adoption of the advanced CTAP imaging increased per-patient imaging costs by 1.19% ($9.28/$779.72), increased per-patient treatment costs by 33.25% ($729.96/$2,195.24), and decreased other per-patient acute care costs by 0.7% (–$114.12/$16,285.85). The large increase in treatment costs was caused by higher proportion of patients being treated. However, improved outcomes lowered the other per-patient acute care costs. Over the five-year period, advanced CTAP imaging led to 1.63% (66/4,040) more patients with good outcomes (90-day mRS 0-2), 2.23% (66/2,960) fewer patients with poor outcomes (90-day mRS 3-5), and no change in mortality (90-day mRS 6). Our CT equipment utilization analysis showed that the demand for CT equipment in terms of scanner time (minutes) was 24% lower in the advanced CTAP imaging strategy compared to the standard-of-care strategy. The number of EVT procedures performed at the CSC may increase by 50%. Conclusions: Our study reveals that adoption of advanced CTAP imaging at presentation increases the demand for treatment of acute ischemic stroke patients as more patients are diagnosed within the treatment time window compared to standard-of-care imaging. Advanced imaging also leads to more patients with good functional outcomes and fewer patients with dependent functional status.